MiR-184 regulates insulin secretion through repression of Slc25a22 - Sumiyo Morita; Takuro Horii; Mika Kimura; Izuho Hatada (PeerJ, 2013)
Insulin secretion from pancreatic β-cells plays an essential role in blood glucose homeostasis and type 2 diabetes. Many genes are involved in the secretion of insulin and most of these genes can be targeted by microRNAs (miRNAs). However, the role of miRNAs in insulin secretion and type 2 diabetes has not been exhaustively studied. The expression miR-184, a miRNA enriched in pancreatic islets, negatively correlates with insulin secretion, suggesting that it is a good candidate for miRNA-mediated regulation of insulin secretion. Here we report that miR-184 inhibits insulin secretion in the MIN6 pancreatic β-cell line through the repression of its target Slc25a22, a mitochondrial glutamate carrier. Our study provides new insight into the regulation of insulin secretion by glutamate transport in mitochondria.